Computed tomography angiography assessment of the degree of simple coarctation of the aorta and its relationship with surgical outcome: A retrospective analysis - Xiao, Hui-Jun; Zhan, A-Lai; Huang, Qing-Wen; Huang, Rui-Gang; Lin, Wei-Hua (Frontiers in Pediatrics, 2022)
Objective: To investigate the correlation between the degree of aortic coarctation and surgical prognosis in infants with simple coarctation of the aorta (CoA) using computed tomography angiography (CTA). Methods: This study was a retrospective study. Twenty-seven infants with simple CoA who underwent surgical correction from January 2020 to June 2022 were enrolled. Aortic diameters were measured at five different levels and normalized to Z scores based on the square root of body surface area. The relevant data were collected and analyzed, and the predictors associated with surgical outcome were determined. Results: Patients were divided into the mild CoA group and the severe CoA group according to the severity of coarctation. The mechanical ventilation duration and the length of ICU stay in the mild CoA group were significantly lower than those in the severe CoA group. Multiple linear regression analyses revealed that the degree of aortic coarctation was a significant risk factor for a prolonged postoperative ICU stay. In addition, gestational age and age at operation were risk factors for a prolonged postoperative ICU stay. Correlation analysis showed that the degree of aortic coarctation correlated with the Z scores of the ascending aorta and postcoarctation aorta. Conclusion: The degree of the CoA is an important predictor of surgical outcomes in infants with simple CoA and was significantly correlated with the ascending aorta and postcoarctation aorta Z scores. Therefore, preoperative CTA should be routinely performed to assess the degree of aortic coarctation and better identify risk factors.